Success factors of institutional repositories (IR) performance in Malaysian academic libraries / Mohd Helmi Masor @ Mansor - Masor @ Mansor, Mohd Helmi (2023)
The purpose of this study is to examine the success factors of institutional repositories and its institutional repositories performance in Malaysian academic libraries. The Institutional Repositories (IR) is a new scholarly communications platform in providing and disseminating digital contents of a university and academic institution. The objectives of the study are: (1) to identify the perception of academicians on the success factors of institutional repositories and its IR performance in Malaysian academic libraries, (2) to compare the success factors of institutional repositories in terms of genders, grade position, education level, years of work experience and work department, (3) to examine the relationship between the success factors of institutional repositories and its IR performance and (4) to measure the effect of success factors on IR performance. This study is a quantitative study using the survey method. The questionnaire was distributed to 357 academicians in five research universities in Malaysia. The research universities are Universiti Malaya (UM), Universiti Teknologi Malaysia (UTM), Universiti Sains Malaysia (USM), Universiti kebangsaan Malaysia (UKM) and Universiti Putra Malaysia (UPM). Respondents are academicians from various faculties and fields starting from grade DS 45 until VK (Professor). From the total respondents of 357, only 257 (71.9%) of the questionnaires were returned and useable for further analysis by Statistical Package for the Social Sciences (SPSS).